RANCANG BANGUN ALAT FERMENTOR PUPUK CAIR (PEMANFAATAN LIMBAH SAYURAN DAN ECENG GONDOK (Eichhornia crassipes) MENJADI PUPUK CAIR DENGAN MENGGUNAKAN AKTIVATOR EM-4) - Junaidi, Robert; ., Anerasari; Harwanda, Muhammad Sabdian; Sulistyawati, Novia Ayu (Politeknik Negeri Sriwijaya, 2020)
The potential for utilizing vegetable waste and water hyacinth to become organic liquid fertilizer is very good to develop, so can reduce dependence on the use of inorganic fertilizers. This liquid organic fertilizer also has the advantage to improving land quality, although the nutrient content of organic matter is generally lower than chemical fertilizers. However, organic matter in liquid fertilizers chemically increases soil buffering capacity against changes in pH, increases cation exchange capacity, decreases P excitation and acts as a reservoir for secondary and micro elements. In supporting the increase in liquid fertilizer production capacity, the manufacture of liquid fertilizer fermenter is a solution for this problem, where the liquid fertilizer fermenter is designed to have sufficient capacity for the pilot plan scale, which is 20 kg of raw material. The liquid fertilizer fermenter is designed to have temperature control that functions to maintain the optimal conditions for the fermentation process that takes place in decomposing organic raw materials into liquid fertilizer. In addition, there is also a biogas tube which functions to accommodate the methane and CO2 gas produced during the fermentation process, and a strainer which functions to separate liquid fertilizer from the remaining fermentation cellulose fibers. To determine the reliability of the fermenter tool that has been made, a lab for making liquid fertilizer was carried out by varying the addition of the activator EM-4 with variations of 100 ml, 150 ml, and 200 ml. The results showed that the addition of EM-4 activator with variations of 150 ml and 200 ml had met the SNI 2803: 2010 standards related to the NPK content of organic fertilizers. The test results on these variations were nitrogen elements of 0.4% and 0.45%, phosphorus elements were 0.18% and 0.19%, and potassium elements were 0.20% and 0.22%. From these results it can be concluded that the fermenter can be used to produce liquid fertilizer properly.